QIRÃ‚â€™AH MUBÃ‚DALAH APPROACH TO THE QURâ€™AN: The Interpretation of Q.S. al-NisÃ¢â€™ [4]: 34 - Rizki, Wahyu Fahrul (ULUL ALBAB Jurnal Studi Islam, 2020)
This writing is the authorâ€™s reflection on one of social phenomena. When a Khatib (preacher), in his preach, quotes al-NisÃ¢â€™ [4]: 34, he says that â€œA wife can be hit if she disobeys or shows ill-conducts (nushÃ»z) to husbandâ€™s commandâ€. This statement is attention-grabbing because it is not just him, even the latest scholar still definesÂ á¸araba as a hitting, so does in the 2020 edition of the Quran translation published by the Indonesian Ministry of Religion. This surely confronts with Quran basic principles itself that address fairness, equality, and mercy for the entire universe. Hence, the basic problem in this writing is that how to precisely understand or interpret the word á¸araba in that verse, thus, the author proposes a mubÃ¢dalah (reciprocal) approach. The main argument in this writing is the word á¸araba in al-NisÃ¢â€™ [4]: 34 does not mean a hitting but "going" to ask other peopleâ€™s help to solve their household problems. In addition, á¸araba is not just for nushÃ»z wife, but also applied to husband.